PENERAPAN METODE SIX SIGMA GUNA MENGURANGI BIAYA KUALITAS PADA PRODUK CELANA OLAHRAGA - Suteja, Ricky; Kristina, Helena Juliana; Salomon, Lithrone Laricha (Universitas Tarumanagara, 2024)
In modern times, there are many large companies operating in various fields, one of which is a company operating in the industrial sector. This garment factory is a large company located in the Cirebon area which operates in the garment sector. The garment products from this garment factory have been sold nationally and internationally with garments ranging from children's clothing to adult clothing. However, in 2020 this company is focused on producing sports pants garments ordered by buyers in the United States. This factory has produced defects in garment products for the last 2 years with a figure reaching 25% of total production. Therefore, in this research, a product quality improvement strategy was carried out using the Six Sigma (DMAIC) method and examining the quality costs incurred by the company. Defects found in garment factories include pinholes, dirt, wrinkles, broken stitches, poor trimming, and skipping. The most common defect is